Modelo Prolab: Alquilalope, un modelo de negocio de micro movilidad urbana basado en economía colaborativa - Delgado Nuñez, Elsa Zoila (2024)
In response to the social issue of increasing urban areas, traffic, and mobility challenges, eco-friendly vehicles have been identified as a tangible solution for the creation of sustainable cities. According to UN-Habitat's 2022 report "The State of the World's Cities," global urbanization will continue to rise, increasing the need for innovative urban mobility solutions. Many individuals own underutilized eco-friendly vehicles, while many others wish to access these vehicles without purchasing them. Therefore, an innovative shared-use business model is proposed with the central premise of connecting owners of underutilized eco-friendly vehicles with those who wish to use them temporarily, through a digital platform. This model addresses the problem of eco-friendly vehicle underutilization, promoting their maximum use and reducing the environmental impact associated with the production and disposal of vehicles that contribute to pollution and traffic (Litman, 2020). Furthermore, it facilitates access to sustainable mobility for individuals who otherwise could not afford to purchase a vehicle. This initiative will contribute to the reduction of traffic congestion and carbon emissions, promoting a more sustainable urban environment and improving people's quality of life. The shared-use platform will generate revenue through transaction commissions, subscriptions, and additional services. Owners of eco-friendly vehicles will earn extra income from renting out their underutilized assets, offsetting associated costs and possibly encouraging the adoption of more environmentally friendly vehicles (Shaheen & Cohen, 2013). Renters will experience significant savings compared to vehicle ownership, without compromising the convenience of accessing eco-friendly transportation when needed. Ultimately, this business model creates a win-win ecosystem for owners, users, and the environment, aligning financial incentives with long-term social and environmental benefits (Sperling, 2018).